KAJIAN SPEKTROFOTOMETRI ULTRA VIOLET UNTUK ANALISIS SPESI IODIUM DALAM GARAM FORTIFIKASI - Yeanchon H Dulanlebit (Molluca Journal of Chemistry Education (MJoCE), 2011)
Iodine is an element nonmetal and essential micronutrient needed by human body in a trace amount. Iodine deficiency may cause brain damage, mental retardation, cretinism and endemic goiter. Analysis method of detecting iodine has widely been used, where iodometry analysis is a standard method to determine iodine content. The analytical performance of iodine determination with a sensitive and selective spectrophotometric method had been evaluated. Iodate reacted with the excessive iodide in an acid medium to form tri-iodide, which can be detected with spectrophotometry at 350 nm. The result of analytical performance evaluation of that method indicated a linearity of standards curve at the range of 1.0-10.0 mg/L, with the R2 value approached one. Result of research, content of iodine in iodized salt sample are 21.45 mg kg-1, 24.88 mg kg-1, 35.42 mg kg-1, 37.98 mg kg-1, 42.84 mg kg-1, dan 57.77 mg kg-1